Phenomenon "LE" and electrophoresis of serum proteins in the study of systemic lupus erythematosus - Stastny M., Pedro (1958)
We present the results of tests and LE electrophoresis of serum proteins made ​​in a number of patients in the course of a study of SLE and related diseases. 120 LE cell research on a group of 83 patients were performed. The test was positive in 29/30 cases of SLE, giving a 96.7%. He was positive also in cases of scleroderma 4/9 investigated (44.4%). All other tests were negative. 100 electrophoretic determinations were made. Serial studies in 34 patients with positive LE test and 20 tests in normal controls assumptions. In cases where the known pattern LES decrease albumin, gamma-globulin increased elevation of prevalent and alpha-2-globulin found. Correlation between clinical improvement and serum proteins was observed. In some cases, significant changes in the levels of serum proteins fractions occurred rapidly. A case where relation between the results of electrophoresis and the temperature of the patient is observed is presented. There was no correlation between serum proteins and the LE phenomenon. The findings described noting the value of both tests in the clinical study of patients are discussed.